Images of the past : Fourth edition - Price, T. Douglas; Feinman, Gary M. (New York : Mcgraw-Hill, 2005)
This well illustrated, full-color, site-by-site survey of prehistory captures the popular interest, excitement, and visual splendor of archaeology as it provides insight into the research, interpretations, and theoretical themes in the field. The new edition maintains the authors' innovative solutions to two central problems of the course: first, the text continues to focus on about 80 sites, giving students less encyclopedic detail but essential coverage of the discoveries that have produced the major insights into prehistory; second, it continues to be organized into essays on sites and concepts, allowing professors complete flexibility in organizing their courses..
Keywords: archaeology -- non-fiction